PENGARUH MEDIA PAPAN BALIK (FLIPCHART) TERHADAP HASIL BELAJAR IPS MATERI PEMANFAATAN SUMBER DAYA ALAM KELAS IV SDN JEPARA 1/90 SURABAYA - Miftakhul Jannah Mita; Savitri Suryandari Savitri; Anna Roosyanti Anna (Fakultas Bahasa dan Sains, Universitas Wijaya Kusuma Surabaya, 2022)
This study aims to describe the effect of Flipchart Media on the social studies learning outcomes of fourth grade students at SDN JEPARA 1/90 Surabaya. The urgency of this research is the need for efforts to improve the quality of the process and student learning outcomes. Social studies learning process that only utilizes learning resources from books and is not interactive can have an impact on student learning outcomes that are not optimal. The approach used is a quantitative approach with experimental research. The type of design used is Quasi Experimental Design. The population used in this study amounted to 72 students and the research sample amounted to 36 students. The data collection used is multiple choice test questions. The test technique used is pre-test and post-test to determine student learning outcomes. Based on data analysis, it is concluded that: 1) There is an effect of using flipchart media on the learning outcomes of fourth grade students at SDN JEPARA 1/90 2021/2022. This is evidenced by the results of hypothesis testing pairs 1 and 2 which reject H0 and accept Ha with a sig value. 2Tailed 0.000 < 0.05.